A política externa brasileira para a argentina durante os governos Fernando Henrique Cardoso e Luiz Inácio Lula da Silva - Ribeiro, Krisna Batista (2017)
The present study analyzes the Brazilian Foreign Policy from 1995 until 2010, period concerning to the governments of the former presidents Fernando Henrique Cardoso and Luiz Inácio Lula da Silva. Our objective is to make an explanation within this period, stating how was the Brazilian external behavior towards the world, in general, and Argentina, in particular, during these two governments, emphasizing the interrelation and the interdependence between the two countries, before their respective idiosyncrasies. The evident interdependence of these two countries over the last few years has flourished in the formation of the Southern Common Market, as well as other bilateral projects - not without a series of obstacles and other proposals for regional integration. We structured our study from the perspective that the understanding of international politics can be well comprehended through the intertwined two-level analysis: the external as well as the domestic sphere, as enunciated by Robert Putnam. We confront this liberal approach to situations in which the relationship between these countries demonstrates that, with short construction of integration projects, a realistic approach to international relations will always be present in foreign policy